2008
DOI: 10.1159/000157879
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hypoplasia as a Cause of Congenital Hypothyroidism in Williams Syndrome

Abstract: In the Williams-Beuren syndrome (WBS), disorders of the thyroid function and morphology have been reported and programs of thyroid screening and surveillance are recommended. However, the frequency of biochemical thyroid assessment, particularly in the first year of life, is being debated. In this report we describe an infant with WBS and congenital hypothyroidism, due to an important thyroid hypoplasia. The patient, a 1-month-old female, negative at primary neonatal thyroid screening, was referred to our hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
(32 reference statements)
2
8
0
Order By: Relevance
“…In all previous reports structural abnormalities of thyroid gland, including thyroid hemiagenesis (Cammareri et al, 1999), sublingual ectopic thyroid (Bini and Pela, 2004) and significant hypoplasia (Stagi et al, 2008), as in our case, have been found. However, in all three cases, neonatal TSH screening was normal and clinical signs and symptoms of hypothyroidism, confirmed by abnormal TSH and T 4 levels, were developed at an advanced age.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In all previous reports structural abnormalities of thyroid gland, including thyroid hemiagenesis (Cammareri et al, 1999), sublingual ectopic thyroid (Bini and Pela, 2004) and significant hypoplasia (Stagi et al, 2008), as in our case, have been found. However, in all three cases, neonatal TSH screening was normal and clinical signs and symptoms of hypothyroidism, confirmed by abnormal TSH and T 4 levels, were developed at an advanced age.…”
Section: Discussionsupporting
confidence: 80%
“…Even in pediatric patients with WS, subclinical hypothyroidism is a frequent finding, either with normal or hypoplastic thyroid gland (Cambiaso et al, 2007). Additionally, a few cases of congenital hypothyroidism due to thyroid hypoplasia or thyroid ectopia can be found in the literature (Bini and Pela, 2004;Cammareri et al, 1999;Stagi et al, 2008). In the majority of these cases, congenital hypothyroidism was not detected at screening test but the diagnosis was established at a more advanced age, preceding the diagnosis of WS by approximately 2 years.…”
Section: Introductionmentioning
confidence: 99%
“…Primary hypothyroidism occurs in about one-third of all patients with WBS8910). About 70% of the patients with hypothyroidism show morphological or volumetric abnormalities of the thyroid gland8910). The major gland abnormality detected in these patients is hypoplasia8910).…”
Section: Discussionmentioning
confidence: 99%
“…About 70% of the patients with hypothyroidism show morphological or volumetric abnormalities of the thyroid gland8910). The major gland abnormality detected in these patients is hypoplasia8910). Unsurprisingly, therefore, most patients have subclinical hypothyroidism8910).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation